The effect of retirement on health behaviours: Evidence from Brazil - Luan Vinicius Bernardelli; Wander Plassa; Michael Alexander Kortt; Michael B. Charles (PLoS ONE, 2025)
Objective This study investigates the impact of retirement on health behaviours in Brazil in light of rising life expectancy and recent pension age reforms, focusing on how retirement affects well-being in a middle-income country. Methods Using data from the 2013 and 2019 Brazilian National Health Surveys (PNS), this study analyses health behaviours among 54,741 individuals aged 50–80. Health behaviours (alcohol consumption, smoking, physical activity, sleep medication use, and diet) were measured using binary and continuous variables. Retirement status was defined as receiving a pension and not working, with Brazil’s minimum retirement age used as an instrumental variable to address endogeneity. Probit and IV probit models for binary outcomes and OLS and IV OLS models for continuous outcomes were estimated, with statistical tests supporting instrument strength and endogeneity. Results The findings reveal a positive relationship between retirement and improvements in health behaviours. In the IV probit models, retirement is associated with increased physical exercise (β = 0.393, p < 0.05) and healthier eating habits (β = 0.371, p < 0.05). Men are less likely than women to reduce smoking. Retirement is linked to greater time spent engaging in physical exercise, reductions in alcohol consumption and smoking, together with healthier eating habits. Conclusion These results have significant policy implications, underscoring the need to consider the potential long-term public health effects of increasing the retirement age, as it could result in higher public health burdens.